Prevalence of HPAI in passerines, woodpeckers and doves presented to the Center for Wild Bird Rehabilitation during the 2022 HPAI H5N1 epizootic - Lundborg, Bren; O'Toole, Grae (Wildlife Rehabilitation Bulletin, 2023)
<span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The Highly Pathogenic Avian Influenza (HPAI) H5N1 clade 2.3.4.4b epizootic affecting North America beginning in late 2021 has affected wild and domestic birds to an unprecedented scale. Mortalities have been documented mainly in raptors, aquatic birds (shorebirds, waterfowl), gulls and other scavenging birds, with rare reports of other species being affected. Passerines, woodpeckers, and doves are not thought to contribute significantly to the transmission of avian influenza, and thus are not regularly tested. Despite this, mortalities and even the possibility of asymptomatic carrier states in songbirds have been documented with HPAI H5N1 strains. This study focused on sampling and testing of species not typically included in HPAI surveillance, to help assess prevalence, symptoms of infection if detected and the possibility of asymptomatic carriers. Throughout two periods in 2022, 164 individuals of 38 species were sampled from Vermont and New Hampshire. None of these birds tested positive for any strain of avian influenza virus. While the scale of this study is small, it highlights the need for testing species that are not a part of regular HPAI surveillance, as well as the role rehabilitation centers may play in that goal.